Penerapan P2TL dan Dinas Jaga Laut Untuk Mencegah Kecelakaan di Laut pada MT. Star Valiant - Asri, Haerani; Rachman, Subehana; Fajri Asri, Muhammad (Dinasti Research, 2024)
The aim of the research is to determine the implementation of guard services to prevent the danger of collisions in MT. Star Valiant complies with procedures. The research was carried out at MT. Star Valiant, from 30 October 2019 to 20 November 2020. This type of research uses descriptive qualitative. The data collection methods used are observation, interviews and documentation studies. The results of the research show that the cause of the implementation of (P2TL) and sea watch service which has not been carried out well on board the ship is because a watch officer has not carried out his watch duties according to the set watch hours. and lack of inspection of navigation tools, especially radar, which must be adjusted to weather conditions and sea conditions.